On Sexualisation and Eroticisation: emancipation of love and lust - Cas Wouters (Universidade Federal do Rio Grande do Sul, 2017)
This paper pursues understanding recent changes in the romantic and sexual relations of young people. Its perspective focuses on the emancipation of women and young people since the 1880s, a moment when social codes dominating the relations between women and men, parents and their children, changed towards greater leniency. Both had to learn how to become sexual subjects as well as sexual objects and to develop a gratifying balance between the two, in trial-and-error processes involving attempts at connecting sexual and relational intimacy in subsequent spurts of sexualisation and eroticisation. The paper sketches significant moments in these processes and raises the question of where we are now.